Social determinants of adolescent smoking over three generations - Doku David; Claro Paulyn; Koivusilta Leena; Rimpelä Arja (SAGE journals, 2022)
Aim: We studied how multigenerational socioeconomic circumstances influence adolescents’ smoking. Previous studies have shown that low academic achievement as well as parents’ low socioeconomic circumstances are associated with adolescents’ smoking, but there are few studies on grandparents’ influence on their grandchildren’s smoking. For the chain of three generations, we hypothesised that high socioeconomic circumstances of both parents and grandparents decrease the probability of smoking and adolescents’ own education and circumstances contribute to this association. We further investigated the role of intergenerational social mobility. Method: Survey data from 1979 to 1997 on 12- to 18-year-old Finns (n=54,487) were linked with 1970–2009 registry-based data of their grandparents, parents and themselves. Socioeconomic circumstances among parents and grandparents were measured by socioeconomic status, education and material resources and among adolescents by academic achievement, educational orientation, family structure and parental smoking. Logistic regression analysis was used to study the associations. Results: Associations of adolescent smoking with grandparental socioeconomic circumstances were weak and mediated through parental circumstances. Parental smoking and divorce and living in a non-intact family increased smoking. Adolescents’ low academic achievement and orientation to low education level were the most important predictors of smoking. Upward intergenerational social mobility between fathers and children decreased the risk of smoking, whereas downward mobility increased it. Conclusions: The influence of grandparents’ low socioeconomic circumstances on grandchildren’s smoking is mediated through parents’ socioeconomic circumstances. Low academic achievement in adolescence is a strong predictor of smoking and adolescents orient towards the group of their future education level, not that of their parents.